EU regulation of e-commerce : a commentary - Lodder, A. R., 1967-; Murray, Andrew, 1972- (Elgar commentaries, 2017)
For the last twenty years the European Union has been extremely active in the field of e-commerce. This important new book addresses the key pieces of EU legislation in the field of e-commerce, including the E-commerce Directive, the Services Directive, the Consumer Directive, the General Data Protection Regulation, and the eID Regulation. The latest in the Elgar Commentaries series, EU Regulation of E-Commerce is the first book to apply this well-established format to a dynamic and increasingly significant area of law. Key features include: - thoroughly up-to-date analysis of decisions of the Court of Justice and the Commission - article-by-article commentary on the latest directives and regulations in the field of e-commerce - a unique structure featuring detailed tables of cases and legislation and paragraph references, enabling easy access to all substantive legal provisions - specially commissioned chapters from leading scholars and practitioners from across the EU. This unique work will provide the definitive account of the essential pieces of EU legislation on e-commerce. Legal practitioners will benefit from the clear structure and close examination of key provisions. The book will also appeal to legal scholars and advanced students, who will appreciate the concise overview and thoughtful analysis on future developments in the field.